1998
DOI: 10.1038/eye.1998.82
|View full text |Cite
|
Sign up to set email alerts
|

Keratocyte density and size in conscious humans by digital image analysis of confocal images

Abstract: Purpose Confocal microscopy can give images of high magnification and resolution in undisturbed living tissue. It provides new information about the cellular structure of the cornea. Our aim was to measure the density, size and distribution of keratocytes.Methods Healthy cornea in four subjects was examined using tandem scanning confocal microscopy. Methods for digital analysis of images were developed.Results Keratocyte density in confocal cross sections was greatest immediately under

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 6 publications
1
18
0
2
Order By: Relevance
“…[58][59][60][61][62] Keratoctye density, in addition, has been reported to decrease with increasing age, 60,62,64 however, other authors 57,63 have reported consistency in the corneal keratocyte populations throughout life. In this study, reduction in keratocyte density with age was found to be significant in the posterior stroma only, with a strong trend within the anterior stroma.…”
Section: 39mentioning
confidence: 99%
“…[58][59][60][61][62] Keratoctye density, in addition, has been reported to decrease with increasing age, 60,62,64 however, other authors 57,63 have reported consistency in the corneal keratocyte populations throughout life. In this study, reduction in keratocyte density with age was found to be significant in the posterior stroma only, with a strong trend within the anterior stroma.…”
Section: 39mentioning
confidence: 99%
“…The methods applied range from manual techniques based on cell marking or cell border tracing [8,13,14] to fully automated cell identification and counting [15][16][17]. The acceptance of CoCM as a method for cell size and density measurements implies validation of the results against equivalent results obtained by histological techniques and knowledge about the reliability and repeatability of the confocal measurements.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Bu çalışmada önceki çalışmaların sonuçlarına benzer şekilde, keratosit dansitelerinde kadın ve erkek cinsiyet arasında anlamlı farklılık görülmemiştir. 10,11,17 Yaş ile birlikte keratosit dansitesinde azalma olduğu ise birçok çalışmada bildirilmiştir.…”
Section: Discussionunclassified